Acute myeloid leukemia resistant to venetoclax-based therapy: What does the future hold?. (May 2023) - Dhakal, Prajwal; Bates, Melissa; Tomasson, Michael H.; Sutamtewagul, Grerk; Dupuy, Adam; Bhatt, Vijaya Raj
Abstract: Venetoclax is a highly selective B-cell lymphoma-2 (BCL-2) inhibitor, which, combined with a DNA hypomethylating agent or low dose cytarabine, results in high rates of initial responses in patients with acute myeloid leukemia (AML). However, the disease relapses in most patients. Mechanisms of resistance to venetoclax-based therapy include TP53 gene mutations or inactivation of p53 protein, activating kinase mutations such as FLT3 and RAS, and upregulation of other BCL-2 family apoptotic proteins. Current clinical trials are exploring strategies such as doublet or triplet regimens incorporating a p53 activator, an anti-CD47 antibody, or other novel agents that target genes and proteins responsible for resistance to venetoclax. Further studies should focus on identifying predictive biomarkers of response to venetoclax-based therapy and incorporating immunotherapeutic approaches such as checkpoint inhibitors, bispecific antibodies, antibody-drug conjugates, and CAR T-cell therapy to improve outcomes for patients with AML.